2017
DOI: 10.1111/cdev.12808
|View full text |Cite
|
Sign up to set email alerts
|

Feel American, Watch American, Eat American? Remote Acculturation, TV, and Nutrition Among Adolescent–Mother Dyads in Jamaica

Abstract: Globalization prompts remote acculturation toward U.S. culture in Jamaica; this study used a bioecological systems approach to examine its proximal impact on nutrition through U.S. cable TV consumption, and maternal influences in the home. Overall, 330 randomly selected adolescent-mother dyads from schools in Kingston, Jamaica (M = 13.8 years, SD = 1.8) completed questionnaires reporting American identity and behavioral preferences, daily time spent watching U.S.-produced TV programs, and frequency of eating u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(75 citation statements)
references
References 66 publications
1
74
0
Order By: Relevance
“…The practices examined in this study are both intertwined with adolescent identities and conceptions of self, and susceptible to change as a result of globalization (Ferguson et al., ; Jensen et al., ; Nguyen & Brown, ). Examining discourses surrounding dietary and linguistic practices has thus afforded a window into the nature of adolescent conceptions of self in relation to local and global cultures, and in relation to social others.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The practices examined in this study are both intertwined with adolescent identities and conceptions of self, and susceptible to change as a result of globalization (Ferguson et al., ; Jensen et al., ; Nguyen & Brown, ). Examining discourses surrounding dietary and linguistic practices has thus afforded a window into the nature of adolescent conceptions of self in relation to local and global cultures, and in relation to social others.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Ferguson et al. () found that Jamaican adolescents with stronger American identity and behavioral practices ate more unhealthy food.…”
Section: The Developmental Psychology Of Globalizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Our multiple‐method research study provides evidence that promotion in outdoor spaces (e.g., billboards, transit advertising) and in places where consumers are buying or procuring food (retail, restaurants) is a tool used by the food industry, especially among low‐nutrient foods and global brands, in the city of Kingston, Jamaica; for a summary, see Table . These findings relate to the evidence that globalization, Americanization in particular, is a recent factor fuelling unhealthy eating in developing countries (Ferguson, Muzaffar, Iturbide, Chu, & Meeks Gardner, ), including Jamaica (Francis et al, ). Food advertising is thought to be a factor contributing to those trends.…”
Section: Discussionmentioning
confidence: 57%